Figurative Language Used in Turnover’s Songs in Peripheral Vision Album - Kadek Suliyasa; Ida Ayu Putri Gita Ardiantari (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This research aims to find out and analyze the types and functions of figurative language used in Turnover's songs in Peripheral Vision album. The researcher used the qualitative method to give a clear description of the problem which is identified. The data were taken from Turnover's song in Peripheral Vision album. The researcher used the theory proposed by Knickerbocker and Reninger (1963) to classify the types of figurative language and the theory proposed by Perrine (1969) to analyze the function of figurative language. The result of this research showed there are 4 types of figurative language used in Peripheral Vision Album by Turnover. There are simile, hyperbole, irony, and metaphor.